Geographies of Violence and Experiences of Re-Existence. The Case of Buenaventura, Colombia, 2005-2015 - Jefferson Jaramillo Marín; Érika Parrado Pardo; Wooldy Edson Louidor (Íconos)
This article analyzes how, in the context of Buenaventura crossed by a variety of violence between 2005 and 2015, some collectives and organizing platforms, mostly composed of young people and women, managed to defend life and imagine the future. It centers on contemporary critical perspectives of social theory and on the construction of two analytical categories: re-existence and geographies of violence. The methodological design included a qualitative work of observation in situ, mapping cases, analyzing context and interviews with leaders and local protagonists. This research proposes a reading of the context of Buenaventura as a paradoxical territory where armed orders and social and economic regimes of violence are interwoven, which are challenged and reinvented by practices of re-existence through political, creative and everyday daily repertoires.